Carbon footprints of European dairy farming: the role of drained peatlands in GHG assessments - Anna-Lena Müller; Ralf Kiese; Clemens Scheer (npj Sustainable Agriculture)
Abstract Climate change is driven by rising greenhouse gases, with food systems contributing a third of emissions. Dairy farming plays a key role, yet LCAs often omit emissions from drained peatlands, which are estimated to release an average of 31.7t CO₂-eq/ha/year used as grasslands. This review highlights the need to integrate soil organic carbon losses into LCAs, as their omission distorts carbon footprints and hinders effective mitigation strategies for reducing dairy-related greenhouse gas emissions.